Physiological and Biochemical Responses of Cucumis melo L. Chloroplasts to Low-Phosphate Stress - Li, Pengli; Weng, Jinyang; Zhang, Qing; Yu, Liyao; Yao, Qi; Chang, Liying; Niu, Qingliang (Frontiers in Plant Science, 2018)
Phosphate (Pi) is often one of the limiting nutrients for plants in soil. Long-term low inorganic phosphate causes irreversible damage to plant cells and limits plant growth. Plants have evolved a series of adaptive responses to circumvent the potential damaging effects of low-Pi stress on living, such as biochemical, physiological and developmental changes. However, the research on the response of photosynthetic organelle to low-Pi stress is scarce. In this research, we investigated the responses of photosynthetic organelle to low-Pi by means of physiological and biochemical analysis. The results indicated that the growth of melon seedling was hampered and dry matter accumulation reduced by low-Pi stress. Low-Pi stress compelled the light intercepted excessive for melon’s actual processing capacity, thereby leading to the reduction of net photosynthesis. The relative electron transport rates and actual quantum yield of photo system were significantly decreased by low-Pi stress with analyzing the chlorophyll fluorescence data. To mitigate the photo inhibition, melon started up the non-photochemical quenching of chlorophyll fluorescence (NPQ) to dissipating excess excitation energy. Meanwhile, low-Pi disrupted the normal photosynthetic electron transport pattern by inhibiting cyclic and non-cyclic electron transport, promoting pseudo-ring electron transport, thus leading to reactive oxygen production in leaves. The reactive oxygen scavenging enzymes activity analysis revealed that the activity was significantly improved by low-Pi to counterbalance the deleterious effects of reactive oxygen species. However, the malondialdehyde content and less developed membrane system of thylakoid observed from ultrastructural chloroplast indicated that these mechanisms failed to keep redox homeostasis and leaves suffered from photo-oxidative stress symptoms. Based on these experimental results we concluded that low-Pi inhibited the activity of photosyetem and further caused photo-oxidative stress and photo inhibition. To alleviate the negative effect, NPQ mechanism, alternative electron transport pathways and antioxidant system were activated to protect the photosynthetic organelles.